The Indian Civil Service and Indian Foreign Policy, 1923-1961 (Taylor & Francis, 2021)
Nehruvian Diplomacy, Indian diplomacy, Cold War politics, decolonisation, British India, World War II, Gandhi
English
Keywords: National liberation and independence; Public administration; Nehruvian Diplomacy, Indian diplomacy, Cold War politics, decolonisation, British India, World War II, Gandhi